2018
DOI: 10.1111/1348-0421.12578
|View full text |Cite
|
Sign up to set email alerts
|

After 18 months of antiretroviral therapy, total HIV DNA decreases more pronouncedly in patients infected by CRF01_AE than in those infected by subtype B and CRF07_BC

Abstract: Whether the amount of HIV DNA is associated with the subtype of HIV-1 after antiretroviral therapy (ART) has not been reported. In the present study, the amount of HIV DNA and RNA and CD4+T counts in blood and semen prior to and after 18 months of ART were compared in 48 patients infected by CRF01_AE, subtype B or CRF07_BC of HIV-1. Viral RNA was suppressed and CD4 cell count recovery achieved in all patients. The level of HIV DNA were similar before ART; however, patients with CRF01_AE had less HIV DNA after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In our study, although the HIV-1 DNA level in both groups declined significantly after ART (Figure 1c&1d), the CRF01_AE subtype exhibited a higher level at baseline, which may explain the higher DNA levels observed at week 96 (Figure 1d). In contrast, Lu performed a study of 48 patients in Guangxi province (China), followed for 18 months and found the decline in total HIV-1 DNA was significantly faster among patients with the CRF01_AE subtype than in those with subtypes B and CRF07_BC [25]. The ratio of CXCR4-usage for clones from CRF01_AE in our study was higher than that of non-CRF01_AE subtypes (Table S1), which is similar to Lu's study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, although the HIV-1 DNA level in both groups declined significantly after ART (Figure 1c&1d), the CRF01_AE subtype exhibited a higher level at baseline, which may explain the higher DNA levels observed at week 96 (Figure 1d). In contrast, Lu performed a study of 48 patients in Guangxi province (China), followed for 18 months and found the decline in total HIV-1 DNA was significantly faster among patients with the CRF01_AE subtype than in those with subtypes B and CRF07_BC [25]. The ratio of CXCR4-usage for clones from CRF01_AE in our study was higher than that of non-CRF01_AE subtypes (Table S1), which is similar to Lu's study.…”
Section: Discussionsupporting
confidence: 83%
“…The ratio of CXCR4-usage for clones from CRF01_AE in our study was higher than that of non-CRF01_AE subtypes (Table S1), which is similar to Lu's study. As to the reason why HIV-1 DNA level of 96 weeks of ART in CRF01_AE subtype is in contrast with those of Lu et al [25], other parameters such as the difference of baseline characteristic or HLA typing might also contribute to the discrepancy.…”
Section: Discussionmentioning
confidence: 62%
“…The ratio of CXCR4-usage for clones from CRF01_AE in our study was higher than that of non-CRF01_AE subtypes (Additional file 1: Table S1), which is similar to Lu's study. As to the reason why HIV-1 DNA level of 96 weeks of ART in CRF01_AE subtype is in contrast with those of Lu et al [25], other parameters such as the difference of baseline characteristic or HLA typing might also contribute to the discrepancy.…”
Section: Discussionmentioning
confidence: 62%
“…1d). In contrast, Lu performed a study of 48 patients in Guangxi province (China), followed for 18 months and found the decline in total HIV-1 DNA was significantly faster among patients with the CRF01_ AE subtype than in those with subtypes B and CRF07_ BC [25]. The ratio of CXCR4-usage for clones from CRF01_AE in our study was higher than that of non-CRF01_AE subtypes (Additional file 1: Table S1), which is similar to Lu's study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation